UNIQUE LARGE-SCALE RESEARCH FACILITIES "SEISMIC INFRASOUND ARRAY FOR MONITORING ARCTIC CRYOLITOZONE AND CONTINUOUS SEISMIC MONITORING OF THE RUSSIAN FEDERATION, NEIGHBOURING TERRITORIES AND THE WORLD" - R. A. Dyagilev; I. A. Sdelnikova; Р. А. Дягилев; И. А. Сдельникова (Frontiers in Marine Science, 2022)
The description of the Unique Large-Scale Research Facilities "Seismic infrasound array for monitoring Arctic cryolithozone and continuous seismic monitoring of the Russian Federation, neighbouring territories and the world" (URF SIA MAC), its hardware and software components are presented. Methods and principle areas of research carried out using the URF are outlined. The URF SIA MAC includes 364 seismic stations throughout Russia and three infrasound arrays. The data obtained at the URF serve to provide domestic fundamental and applied research in the field of Earth Sciences (seismology, geophysics, geodynamics, geoecology) and to study catastrophic events of a natural induced nature. The modern URF data archive includes digital seismic records since 1993. In addition, there is a significant amount of analogue records (since 1904) available for further digitization. The URF SIA MAC provides seismological data to many Russian scientific, research and design organizations. The article presents the main results of the Federal Research Centre Geophysical Survey of the Russian Academy of Sciences obtained in recent years using the URF data. Представлено описание уникальной научной установки «Сейсмоинфразвуковой комплекс мониторинга арктической криолитозоны и комплекс непрерывного сейсмического мониторинга Российской Федерации, сопредельных территорий и мира» (УНУ СИЗК МАК), eе аппаратной и программной компонент, описаны методы и основные направления исследований, проводимые с ее использованием. В состав установки входит 364 сейсмические станции, расположенные на всей территории России, и три инфразвуковые группы. Данные, получаемые на УНУ, служат для обеспечения отечественных фундаментальных и прикладных исследований в области наук о Земле (сейсмология, геофизика, геодинамика, геоэкология), а также для изучения катастрофических событий природного и техногенного характера. Современный архив данных УНУ включает цифровые сейсмические записи начиная с 1993 г.; кроме того, имеется значительный объем аналоговых записей ...